P wave axis and its correlation with severity of chronic obstructive pulmonary disease - R., Prasuna K.; Ratnam, Praveena Korani; R., Pramod Kumar K.; V. K., Krishna Kumar T. (International Journal of Advances in Medicine, 2020)
Background: COPD can affect the heart as secondary effects of the disease. The electrocardiography has been seen as a very best tool for early diagnosis of any cardiac changes that may occur as a result of secondary effects of the chronic obstructive pulmonary disease. Objective of the study was to study the P wave axis and its correlation with severity of COPD. Methods: Here, 30 Patients of COPD confirmed by clinical history, examination and Pulmonary function tests were included in the study. These patients were clinically examined, and they underwent routine investigations like hemogram, urine examination, blood urea, serum creatinine, chest x-ray, random blood sugar, sputum examination and ABG analysis. These patients underwent pulmonary function test, ECG and ECHO. Results: In this study 36.66% of patients had RVH. Incomplete RBBB was seen in 20%. 13.33% had normal ECG. Most common finding in patients with less than one year of exposure was RVH. Low voltage complexes and R/S ratio in V1>1 were the only ECG changes with significant correlation with severity of the disease (p<0.05). Maximum no. of patients had a P wave axis of 71-800. the correlation between P wave axis and the duration of the disease was found to be statistically significant. the correlation between P wave axis and the severity of the disease was found to be statistically significant, 8/27 patients (29.63%) with less than one year of disease had features of corpulmonale. Conclusions: P-axis verticalization can serve as a very effective electrocardiographic screening tool for emphysema in the general population.